The impact of gender on the risk of cardiovascular events in older adults with advanced chronic kidney disease - EQUAL study investigators (Oxford University Press, 2023)
Background. Patients with chronic kidney disease (CKD) are at a higher risk of major adverse cardiovascular events (MACE) compared with the general population, but gender differences in this risk, especially in older adults, are not fully known.We aim to identify gender differences in the risk of MACE in older European CKD patients, and explore factors that may explain these differences. Methods. The European Quality study (EQUAL) is a prospective study on stage 4-5 CKD patients, ≥65 years old, not on dialysis, from Germany, Italy, the Netherlands, Poland, Sweden and the UK. Cox regression and cumulative incidence competing risk curves were used to identify gender differences in MACE risks. Mediation analysis was used to identify variables which may explain risk differences between men and women. Results. A total of 417 men out of 1134 (37%) and 185 women out of 602 women (31%) experienced at least one MACE, over a follow-up period of 5 years.Women had an 18% lower risk of first MACE compared with men (hazard ratio 0.82; 95% confidence interval 0.69-0.97; P = .02), which was attenuated after adjusting for pre-existing cardiometabolic comorbidities and cardiovascular risk factors. There were no significant gender differences in the risk of recurrent MACE or fatal MACE. The risk difference in MACE by gender was larger in patients aged 65-75 years, compared with patients over 75 years. Conclusions. In a cohort of older adults with advanced CKD, women had lower risks of MACE. These risk differences were partially explained by pre-existing cardiometabolic comorbidities and cardiovascular risk factors.
Keywords: cardiovascular events; chronic kidney disease; gender differences; older adults; risk differences; Nephrology; Transplantation